Organizational characteristics and processes are important in the adoption of the Alberta Nutrition Guidelines for Children and Youth in child-care centres. Issue 9 (22nd October 2014) - Farmer, Anna P; Nikolopoulos, Hara; McCargar, Linda; Berry, Tanya; Mager, Diana
Abstract: Objective: The objective of the present study was to gain an understanding of the organizational characteristics and processes in two child-care centres that may influence adoption of the Alberta Nutrition Guidelines for Children and Youth (ANGCY). Design: In-depth qualitative case studies. Data were collected through direct observations, key informant interviews and field notes. Diffusion of Innovations theory guided the evaluation and intrinsic case analysis. Setting: Two urban child-care centres in Edmonton, Alberta, Canada identified as exemplary early adopter cases. Subjects: Ten key informants comprised of directors, junior and senior staff members participated in interviews. Results: Organizational processes such as leadership, networking and knowledge brokering, health champions and organizational culture positively influenced adoption behaviour in child-care centres. A key determinant influencing organizational behaviour within both centres was the directors' strong leadership. Acceptance of and adherence to the guidelines were facilitated by organizational factors, such as degree of centralization, formalization and complexity, level of staff training and education. Knowledge brokering by directors was important for transferring and exchanging information across the centre. All child-care staff embraced their informal role as health champions as essential to supporting guideline adherence and encouraging healthy food and eating environments. Conclusions: Organizational processes and characteristics such as leadership, knowledge brokering and networking, organizational culture and health champions played an important role in the adoption of nutrition guidelines in child-care centres. The complex interplay of decision making, organization of work and specialization of roles influenced the extent to which nutrition guidelines were adopted.